THE EFFECT OF DICTOGLOSS ON STUDENTS’ LISTENING ACHIEVEMENT - Dyah Aminatun; Pipit Muliyah; Haryanti Haryanti (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
Listening is one of important skills the students should posses in learning English as a foreign language. Listening has a vital role in learning a foreign language especially in communication since most of the students’ activities involve listening. Unfortunately, students’ listening comprehension did not reach a good result. This study was conducted to reveal the effect of dictogloss to improve students’ listening achievement. The design of this study was a quasi-experimental study. The samples were chosen from the second grade students at SMA Negeri 1 Pandeglang by using purposive sampling. The experimental class was taught by implementing dictogloss, while the control class was taught without dictogloss. A test was administered as the primary instrument to collect the data. The final mean scores gained from both classes were analyzed by using t-test at a significance level of α = 0.05. It was found that the mean score of experimental class was 67.6, while the control class was 59.96. The statistical calculation of gained score revealed that the t-count was 2.53, and the t-table was 1.668 at a significant level of α = 0.05. This showed that the t-count was higher than t-table. It implied that there was a significance difference of two mean scores gained. Therefore, it could be concluded that dictogloss provided positive influence on students’ listening achievement, and it could be an alternative technique to be used in teaching listening in the classroom.